Underwater radiance distributions measured with miniaturized multispectral radiance cameras - Antoine, David; Morel, A.; Leymarie, E.; Houyou, A.; Gentili, B.; Victori, S.; Buis, J.; Buis, N.; Meunier, S.; Canini, M.; Crozel, D.; Fougnie, B.; et al. (American Meteorological Society, 2013)
Miniaturized radiance cameras measuring underwater multispectral radiances in all directions at high-radiometric accuracy (CE600) are presented. The camera design is described, as well as the main steps of its optical and radiometric characterization and calibration. The results show the excellent optical quality of the specifically designed fish-eye objective. They also show the low noise and excellent linearity of the complementary metal oxide semiconductor (CMOS) detector array that is used. Initial results obtained in various oceanic environments demonstrate the potential of this instrument to provide new measurements of the underwater radiance distribution from the sea surface to dimly lit layers at depth. Excellent agreement is obtained between nadir radiances measured with the camera and commercial radiometers. Comparison of the upwelling radiance distributions measured with the CE600 and those obtained with another radiance camera also shows a very close agreement. The CE600 measurements allow all apparent optical properties (AOPs) to be determined from integration of the radiance distributions and inherent optical properties (IOPs) to be determined from inversion of the AOPs. This possibility represents a significant advance for marine optics by tying all optical properties to the radiometric standard and avoiding the deployment of complex instrument packages to collect AOPs and IOPs simultaneously (except when it comes to partitioning IOPs into their component parts).